Study of indications and post-operative complications of primary caesarean section in tertiary care hospital in Nepal - Rajbhanadary, Sanyukta; Shrivastava, Veena Rani (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Caesarean section performed for appropriate obstetric or medical indications are life saving for both mother and new born. But its advantage does not justify its continuous increase as it is a major surgical procedure associated with maternal and fetal complications. The main objective of this study was to study the indications of primary caesarean section and its maternal and fetal complications in Nepal medical college teaching hospital (NMCTH). Methods: This is a hospital based cross sectional study carried out for a period of one year from 1st October 20113 to 30th September 2014 in department of obstetrics and gynecology in NMCTH Nepal. The study included 183 primary caesarean cases enrolled as per the inclusion criteria. The indications for caesarean section, associated maternal and fetal complications were noted. Results: The rate of caesarean section during the study period was 21.40%. The study included 183 patients who underwent primary caesarean section, 162 (88.5%) cases were emergency cases and 21 (11.5%). Cases were elective cases. The most common indications were fetal distress (n-74, 40.4%) followed by cephalo pelvic disproportion (n-27, 14.8%). The maternal complications seen were urinary tract infection (n-34, 68%), wound infection (n-12, 24%), post-partum hemorrhage (n-3, 6%). The common fetal complications noted were apgar score of less than 7 (n-7, 31.8%), transient tachypnea of newborn (n-6, 27.27%) and meconium aspiration syndrome (n-4, 18.18%). Conclusions: Emergency primary caesarean section was proportionally higher than elective caesarean section. It was also associated with more maternal and fetal complications.